Values and Organizational Principles of the «Plast» in Olexander Tysovskyʼs Views (1886-1968) - Mykola Solovey (Pedagogical Discourse, 2013)
The article analyzes Olexander Tysovskyʼs views on values and organizational conditions of a personality upbringing in the Ukrainian scout organization «Plast». O.Tysovsky put the idea of loyalty to God and Ukraine to the basis of the «Plast» activity. The derivatives were moral principles: to help others and to comply with the laws of the «Plast». According to O.Tysovsky the achievement of a certain ideal is possible due to self-cultivation, overcoming of physical and mental obstacles, tempering the will and character, performance of his duty. The cornerstones of formation of «Plast» member’s moral consciousness and the value ​​ attitude to themselves, people and life in general were the «Plast» laws. In organizational terms the mastery of the laws was based on three testing stages. As the highest degree of perfection O.Tysovsky proposed tytutyly «Hetman scout – skob» and «Honorary scout». Their goal was to prepare young people in different disciplines and professions that have practical importance in everyday life, given the opportunity to be successful, enterprising, and ready to serve the community and homeland.